Proceedings of the 16th International Workshop on Semantic Evaluation (SemEval-2022) 2022
DOI: 10.18653/v1/2022.semeval-1.176
|View full text |Cite
|
Sign up to set email alerts
|

SemEval-2022 Task 9: R2VQ – Competence-based Multimodal Question Answering

Abstract: In this task, we identify a challenge that is reflective of linguistic and cognitive competencies that humans have when speaking and reasoning. Particularly, given the intuition that textual and visual information mutually inform each other for semantic reasoning, we formulate a Competence-based Question Answering challenge, designed to involve rich semantic annotation and aligned text-video objects. The task is to answer questions from a collection of English language cooking recipes and videos, where each qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Verbs from the analyzed part are collected using either SRL (more specifically, tokens labeled as B-V), or a CRL and SRL combination, namely finding B-EVENT (CRL) with corresponding SRL (I-V or D-V). A detailed description of the annotation system is presented in Tu et al (2022).…”
Section: Intent Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Verbs from the analyzed part are collected using either SRL (more specifically, tokens labeled as B-V), or a CRL and SRL combination, namely finding B-EVENT (CRL) with corresponding SRL (I-V or D-V). A detailed description of the annotation system is presented in Tu et al (2022).…”
Section: Intent Identificationmentioning
confidence: 99%
“…The goal of the task 1 was to develop a system applying existing knowledge to new situations, demonstrating a kind of understanding of a real-world domain. The competition presents a QA 2 challenge requiring linguistic and cognitive competencies that humans have while speaking and reasoning (Tu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The R2VQ (Tu et al, 2022) task proposed the use of multimodal models to leverage both text and image for QA in the context of recipes. The R2VQ task adopts the definition of 'Question Family' from the CLEVR dataset (Johnson et al, 2017), where each type of question-answer pair comes from a template identified by task organisers.…”
Section: Task and Datamentioning
confidence: 99%
“…In this paper, we discuss an approach to the Question Answering (QA) task for SemEval-2022 Task9 (Tu et al, 2022). This task is structured as question answering pairs, querying how well a system understands the semantics of recipes derived from a collection of English cooking recipes and videos, which involve rich semantic annotation and aligned text-video objects.…”
Section: Introductionmentioning
confidence: 99%